NATURAL REGENERATION OF POST FIRE LOWLAND TROPICAL FORESTS IN THE GRAND FOREST PARK SULTAN THAHA SYAIFUDDIN JAMBI - Nursanti, Nursanti; Saleh, Zuhratus; Ulfa, Maria Ulfa (Department of Forest Resources Conservation and Ecotourism - IPB University, 2023)
Indonesia's lowland tropical rain forests are rich in endemic species. One of the problem is lowland forests often experience degradation due to excessive exposure and forest fire. Sultan Thaha Syaifuddin Grand Forest Park or Tahura STS is a part of tropical lowland forests which often experience fires, thus reducing its quality so it needs to be restored with regeneration efforts. The purpose of this study is to get data and information about the potential for lowland forest regeneration in Tahura STS after forest fires. This research was conducted for 8 months from March to October 2021 with location in Tahura STS and Jambi University. Researchers were carried out by making a 20x20 meter nested plot placed on 5 transects along 300 meters for each transect. Each transect contains 6 plots with a placement of 50 meters between plots. From research in the field obtained as many as 143 plant species from various growth stages ranging from seedlings, stakes, poles, trees and basic ground vegetation. These results indicate that the diversity of plants in Tahura STS is high to moderate while the evennes index shows that the plant community in Tahura STS is a stable community. In the early stages it can be concluded that the potential for natural regeneration in Tahura STS is very likely to occur as long as the damaging process is reduced and eliminated.